Faixas de controle de plantas daninhas e seus reflexos no crescimento de plantas de eucalipto - De Toledo, Roberto Estêvão Bragion; Victoria Filho, Ricardo; Da Costa Aguiar Alves, Pedro Luís [UNESP]; Pitelli, Robinson Antonio [UNESP]; Lopes, Marco Aurélio Freitas (My University, 2003)
Two field trial were conducted in Eucalyptus grandis W. Hill ex Maiden x Eucalyptus urophylla S.T. Blake crops at Três Lagoas, Mato Grosso do Sul State and Brotas, São Paulo State, Brazil, to evaluate the effects of weed control in strip of different width on the Eucalyptus plant growth. The experiments consisted of two groups treatments: group 1 - with constant width control strips being kept during the first 12 months, i.e., at 0, 25, 50, 100, 125 and 150cm on each side of the Eucalyptus row and, group 2: with increasing width control strips being adopted along the experimental period, i.e., at 25 to 150, 25-50-150, 50 to 150, 50-125-150, 100-125-150, 100 tot 150 and 125 to 150 cm on each side of the Eucalyptus row during the first 12 months. At 49 moths after planting it was verified that the Eucalyptus plants that had grown both in the constant and increasing width control strips, equal to or higher than 100 and 50 cm, respectively, showed higher steam diameter, plant height, volume and annual increment average of wood. These results led to the conclusion that the minimum control strip width should be 100 cm on each side of the Eucalyptus row in order to keep the crop free of weed interference.
Weed control strip on Eucalyptus plants growth
Keywords: Brachiaria decumbens; Competition and interference; Eucalyptus; Weed control; Plant stems; Plantations; Growth kinetics; Hardwoods; Plants (botany); Volume measurement; Forestry